2015
DOI: 10.1021/acs.jpcb.5b04779
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Filament Supramolecular Chirality Reversal of HET-s (218–289) Prion Fibrils Driven by pH Elevation

Abstract: Amyloid fibril polymorphism is not well understood despite its potential importance for biological activity and associated toxicity. Controlling the polymorphism of mature fibrils including their morphology and supramolecular chirality by postfibrillation changes in the local environment is the subject of this study. Specifically, the effect of pH on the stability and dynamics of HET-s (218-289) prion fibrils has been determined through the use of vibrational circular dichroism (VCD), deep UV resonance Raman, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…The VCD spectrum covers the infrared and near-infrared regions of the circular dichroism spectrum. [17][18][19][20][21] A large number of bands due to the normal modes are utilized to analyze the molecular vibrations of a given molecule in order to determine its detailed conformation. Another advantage of the method is that even a molecule with no electronic absorption in the UV-visible region can be a target.…”
Section: Strategy In Applying the Vcd Methods To Gelsmentioning
confidence: 99%
“…The VCD spectrum covers the infrared and near-infrared regions of the circular dichroism spectrum. [17][18][19][20][21] A large number of bands due to the normal modes are utilized to analyze the molecular vibrations of a given molecule in order to determine its detailed conformation. Another advantage of the method is that even a molecule with no electronic absorption in the UV-visible region can be a target.…”
Section: Strategy In Applying the Vcd Methods To Gelsmentioning
confidence: 99%
“…Empirically, five VCD signature bands in the amide I (C=O stretching, ∼1650 cm −1 ) and amide II (CN stretching, ∼1530 cm −1 ) regions were ascribed to amyloid fibril aggregation, but VCD patterns of different signs and shapes were found for various proteins and peptides . Even for the same protein, a slight variation in fibril preparation may significantly affect their morphology and VCD …”
Section: Vibrational Circular Dichroismmentioning
confidence: 99%
“…Beyond the intramolecular and intermolecular factors, there are also various external stimuli that can modulate supramolecular chirality, such as heat, pH, light, sonication, and solvents, and provide abundant references for dynamic tuning . Feringa et al.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%
“…Beyondt he intramolecular and intermolecular factors, there are also various external stimuli that can modulate supramolecular chirality,s uch as heat, [30] pH, [31] light, [32] sonication, [33] and solvents, [34] and provide abundant references for dynamic tuning. [35] Feringa et al reported reversible chirality control by using UV and visible light in as elf-assembling molecular system based on ad ithienylethene photochromic unit functionalized with (R)-1-phenylethylamine-derived amides, in which molecular and supramolecular chirality could communicate.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%